Performance of Plasma Amyloid β, Total Tau, and Neurofilament Light Chain in the Identification of Probable Alzheimer's Disease in South China - Jiao, Bin; Liu, Hui; Guo, Lina; Liao, Xinxin; Zhou, Yafang; Weng, Ling; Xiao, Xuewen; Zhou, Lu; Wang, Xin; Jiang, Yaling; Yang, Qijie; Zhu, Yuan; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Alzheimer’s disease (AD) is the most common type of dementia and no effective treatment to date. It is essential to develop a minimally invasive blood-based biomarker as tools for screening the general population, but the efficacy remains controversial. This cross-sectional study aimed to evaluate the ability of plasma biomarkers, including amyloid β (Aβ), total tau (t-tau), and neurofilament light chain (NfL), to detect probable AD in the South Chinese population. Methods: A total of 277 patients with a clinical diagnosis of probable AD and 153 healthy controls with normal cognitive function (CN) were enrolled in this study. The levels of plasma Aβ42, Aβ40, t-tau, and NfL were detected using ultra-sensitive immune-based assays (SIMOA). Lumbar puncture was conducted in 89 patients with AD to detect Aβ42, Aβ40, t-tau, and phosphorylated (p)-tau levels in the cerebrospinal fluid (CSF) and to evaluate the consistency between plasma and CSF biomarkers through correlation analysis. Finally, the diagnostic value of plasma biomarkers was further assessed by constructing a receiver operating characteristic (ROC) curve. Results: After adjusting for age, sex and APOE alleles, compared to the CN group, the plasma t-tau and NfL were significantly increased in the AD group (p<0.01, Bonferroni correction). Correlation analysis showed that only the plasma t-tau level was positively correlated with the CSF t-tau levels (r=0.319, p=0.003). The diagnostic model combining plasma t-tau and NfL levels, as well as age, sex and APOE alleles, showed the best performance for the identification of probable AD (area under the curve (AUC) = 0.89, sensitivity = 82.31%, specificity = 83.66%). Conclusion: Blood biomarkers can effectively distinguish probable AD patients from controls and may be a non-invasive and efficient method for AD pre-screening.